TEACHING FUTURE TEACHERS FOR DEVELOPING PUPILS’ CRITICAL THINKING IN ENGLISH LANGUAGE CLASSROOM - Гулич, Марія (SWorldJournal, 2026)
The research is devoted to the study of the theoretical and practical foundations of preparing future English language teachers to foster critical thinking in schoolchildren. The work examines the essence of critical thinking, its role in the development